Пушкинская эпоха = Pushkin's Era - Leibov, Roman; Okhotin, Nikita (Acta Slavica Estonica, 2020)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. Another volume in the long tradition of Tartu Pushkin studies includes works by scholars from Estonia, Russia, USA, Ukraine, the Czech Republic and Switzerland. There are comments on individual texts as well as extensive historical and literary studies. A separate section is devoted to a study that demonstrates the possibilities of the statistical approach to the problems of attribution and dating of poetic texts. The most extensive section contains various biographical and bibliographical material, significantly expanding our understanding of Russian periodicals, Russian-European cultural ties and literary history of the early 19th century.